Exploration of Homeowners' Perception Towards Green Homes Features - M. D. Krisna Adya Anindita; Natalia Suwarno; Dewi Larasati; Hanson Endra Kusuma; Daud Tjondrorahardja (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
Green homes concept implementation is one of strategies to increase energy and water efficiency in residential buildings. Currently, the concept of green homes has been adopted by the public and promoted by the government because of its benefits. Utilization of green home features is known to benefit the environment and occupants. However, as the number of green home users increases, the adoption acceleration of green home features has barriers. Homeowners' perceptions of green home features determine homeowners' attitudes toward utilizing these features. This research aims to identify the hindering factors of green home feature adoption by exploring homeowners’ perceptions. The green home features such as smart lighting and sensor, energy-efficient labeled appliance, photovoltaic panel, water meters, dual-flush toilet, and rainwater harvesting are reviewed. Data was gathered using an online open questionnaire and analyzed using grounded theory method. Result shows green homes features’ adoption barriers consist of technical aspects, product availability, economics, knowledge, regulation, and motivation.